Principle-centred leadership - Covey, Stephen R. (London : Pockets Books, 2002)
How do we as individuals and organizations survive and thrive amid tremendous change? Why are efforts to improve falling so short in real results despite the millions of dollars in time, capital, and human effort being spent on them? How do we unleash the creativity, talent, and energy within ourselves and others in the midst of pressure? Is it realistic to believe that balance among personal, family, and professional life is possible? The answer to these and other dilemmas is Principle-Centered Leadership, a long-term, inside-out approach to developing people and organizations. The key to dealing with the challenges that face us today is the recognition of a principle-centered core within both ourselves and our organizations. Dr. Covey offers insights and guidelines that can help you apply these principles both at work and at home -- leading not just to a new understanding of how to increase quality and productivity, but also to a new appreciation of the importance of building personal and professional relationships in order to enjoy a more balanced, more rewarding, more effective life.
Includes index.
Keywords: Success -- Psychological aspects; Success in business; Leadership